1980
DOI: 10.1007/bf00584198
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH and surface pH in skeletal and cardiac muscle measured with a double-barrelled pH microelectrode

Abstract: The construction of a double-barrelled pH sensitive microelectrode for intracellular use is described. Repetitive measurements of intracellular pH were obtained in rat soleus muscle and sheep Purkinje fibres. They yielded pH values ranging between 7.1 and 7.2 in a CO2/HCO3- buffered medium at 37 degrees C. A lower pH value than that of the bulk solution was found at the surface of the cells using either double-barrelled or single-barrelled pH sensitive microelectrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 4 publications
1
20
2
Order By: Relevance
“…Control values of pH, were found to be similar to those reported by other investigators (26)(27)(28) and were higher than would be predicted from simple passive distribution resulting from the electrochemical gradient across the cell membrane. This transsarcolemmal proton gradient is maintained primarily by Na-H exchange, although there remains some controversy regarding the relative importance of the Cl-HCO3 transport mechanism (29).…”
Section: Methodssupporting
confidence: 86%
“…Control values of pH, were found to be similar to those reported by other investigators (26)(27)(28) and were higher than would be predicted from simple passive distribution resulting from the electrochemical gradient across the cell membrane. This transsarcolemmal proton gradient is maintained primarily by Na-H exchange, although there remains some controversy regarding the relative importance of the Cl-HCO3 transport mechanism (29).…”
Section: Methodssupporting
confidence: 86%
“…Earlier, Furusawa & Kerridge (1927) had measured the pH of cell homogenates and suggested that cat uterine muscle was considerably more alkaline than either cardiac or skeletal muscle. Their method was obviously crude, yet their values for skeletal and cardiac muscle are remarkably similar to those obtained since by direct measurement with pH-sensitive micro-electrodes (Ellis & Thomas, 1976a, b;Aickin & Thomas, 1977a;Vaughan-Jones, 1979;de Hemptinne, 1980). pH-sensitive micro-electrodes clearly can provide the most trustworthy measurements and, in addition, enable continuous recording ofchanges in pHi.…”
Section: Intracellular Ph (Phi) Of the Surface Cells Of Guinea-pig Vamentioning
confidence: 62%
“…The value has been used in the following paper (Aickin & Brading, 1984) where it is notable that the conclusions agree with the assumption of such a low value. (Ellis & Thomas, 1976a, b), 7 09 (Vaughan-Jones, 1979) and 7-1-7-2 (de Hemptinne, 1980) in sheep heart Purkinje fibres, and 7 07 (Aickin & Thomas, 1977 a) and7-1-7-2 (de Hemptinne, 1980) in mouse and rat soleus muscle. The similarity between the muscle types extends to their response to changes in pHo at constant CO2, although the resultant changes in pH, occurred faster in smooth muscle, presumably reflecting the larger surface area to volume ratio of these cells.…”
Section: Calculation Of Intracellular Buffering Powermentioning
confidence: 98%
“…For instance, interstitial acidification at lower buffer concentrations16 may not only reduce arrhythmias by slowing Na+-H+ exchange7; protons also compete with Na+ and Ca 2 for access to their voltage-gated channels. [17][18] Similarly, the antiarrhythmic actions of DMA and HMA need not exclusively be due to inhibition of sarcolemmal Na+-H+ exchange. With prolonged (>5 minutes) exposure, these compounds also have progressive negative chronotropic and vasoconstricting effects (data not shown), which are presumably the result of H+ retention in nodal tissue18 and/or blood vessel walls.…”
Section: Buffering Capacity and Reperfusion Arrhythmiasmentioning
confidence: 99%